Surface modified boron nitride towards enhanced thermal and mechanical performance of thermoplastic polyurethane composite. (1st August 2021) - Bashir, Akbar; Maqbool, Muhammad; Lv, Ruicong; Usman, Ali; Guo, Haichang; Aftab, Waseem; Niu, Hongyu; Liu, Mengjia; Bai, Shu-Lin
Abstract: Owing to the unpredictable advancement in electronic devices, the demand for highly thermally conductive and electrically insulating material is increasing day by day. Besides, surface treatment of chemically inert hexagonal boron nitride (h-BN) sheets found challenging and a distressing contention towards its acceptable thermal transportation. Herein, h-BN sheets are functionalized with divergent amines (its three isomers) to obtain their astonishing properties like high disperse ability and development of interfacial conduction in polymer composite. This comparative study elucidates the significance of the covalent interaction of amines (-NH2 ) with h-BN lattice as well as strong hydrogen bonding with thermoplastic polyurethane (TPU) matrix. It is demonstrated that both ortho -phenylenediamine o -PDA-BN and para -phenylenediamine p -PDA-BN filled TPU composites exhibit higher through-plane thermal conductivity ( ┴ TC) of 2.06 and 1.96 W m −1 K −1 respectively by substantially establishing a higher thermal transportation path at high filler loading of 45 wt %. Whereas, meta -phenylenediamine m -PDA-BN composites reveal somewhat low ┴ TC of 1.27 W m −1 K −1 at the same filler loading. Interestingly, all fabricated composites consisting of functionalized BN (f-BN) and TPU show unprecedented thermal and mechanical properties at such a high filler loading which demonstrates their great potential for packaging application in microelectronics. Highlights: For the first time, we showed a comparative study which explains the introduction of divergent amines (its three isomers) o -PDA, m -PDA, and p -PDA onto the hexagonal boron nitride (h-BN) surface. Our results establish the significance of the covalent interaction of the targeted amino group (-NH2 ) with h-BN lattice. Our findings reveal all (f-BN) composites show unprecedented thermal and mechanical properties at high filler loading. which demonstrates their great potential for packaging applications in microelectronics.